Penerapan Logika Fuzzy Untuk Peramalan Penjualan Cumi–Cumi Menggunakan Metode Fuzzy Time Series Cheng - Agustina, Chaterine; Sriani (STMIK Budi Darma, 2024)
The utilization of fishery resources, especially marine, is currently dominated by community fisheries businesses that usually have a small scale. One of these resources is squid. Squid sales sometimes experience ups and downs, where the ups and downs of sales are influenced by several factors, one of which is bad weather. Therefore, the stock on the market is also getting smaller and the high price also makes buyers decrease. The uncertain need for squid sales every month makes it difficult to determine the amount of squid that will be brought in each month. The main objective of this study is to improve the accuracy of squid sales forecasting and to assist warehouse owners in managing production according to market needs. The results of this study are expected to provide a more accurate picture of squid sales trends in the future, so that they can help in making better business decisions. Fuzzy time series is a data forecasting method that uses fuzzy principles as its basis. In this study, all data amounted to 59 data per day for 3 months. The study was conducted using MATLAB software and using the R programming language to carry out the forecasting process. Compared to the previous one, the next sales increased because the forecast was obtained with a fairly rapid increase. The next squid sales forecasting process based on the dataset owned was 403 Kg. By using the MAPE technique, it is known that the prediction process carried out has an accuracy of 82.3%.